(untitled) (Journal of Human Sciences, 2021)
This study aimed to identify the level of practising the supervisory methods by the educational supervisors at secondary schools in the municipality of Derj, from the teachers’ point of view. At its theoretical part, it has reviewed the supervisory methods in terms of their concept, and their methods, at the secondary stage in the municipality. It also included some previous studies, which related to this study. For achieving the objectives of the study, the researchers have used the descriptive and analytical approach. They have used two tools: the first one; was the Questionnaire, which has been given to male and female teachers’ at the secondary schools in the municipality. The second one; was the Interview which was used with the educational supervisors at this stage. The Questionnaire has been completed with (SPSS) and used the means of statistical calculation using the coefficient of reliability of factor (Alpha Cronbach), as well as calculating averages, using standard deviations, then using the T-test and unilateral variance with variables of the study. This study has shown the following results: At the Questionnaire axles; the responses of secondary schools’ teachers in the municipality of Derj about practising the supervisory methods appeared low. The absence of statistically significant differences at the level 0.05 among teachers’ responses about practising the supervisory methods at the secondary schools in the municipality, in regards to the variables of (gender, specialization, academic qualification, and the duration of experience).In the light of the obtained results, the study has recommended the necessity of expanding the educational supervision methods. Therefore; it has suggested conducting similar studies at other stages, targeting other samples of principals, educational supervisors, and educational officials, besides the teachers.